Formation of directional fluid flows in a vicinity of high-gradient ferromagnetic head in a permanent magnetic field - Gorobets, Oksana; Sorokin, M.; Gorobets, V. Yu.; Bandurka, N. P. (My University, 2001)
The flows of electrolytes in the vicinity of ferromagnetic particles in a constant magnetic field have been investigated.
Keywords: високо градієнтні магнітні поля; высоко градиентные магнитные поля; high gradient magnetic fields; дисперсні частинки; дисперсные частицы; dispersed particles; електроліти; электролиты; electrolytes; кафедра готельно-ресторанної справи